2020
DOI: 10.20944/preprints202011.0465.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Web Unevenness due to Thermal Deformation in Roll–to–Roll Manufacturing Process

Abstract: In roll-to-roll (R2R) processing, uniformity of the web is a crucial factor that can guarantee high coating quality. To understand web defects due to thermal deformation, we analyzed the effects of web unevenness on the coating quality of an yttria-stabilized zirconia (YSZ) layer, a brittle electrolyte of solid oxide fuel cells (SOFCs). We used finite element analysis to analyze the thermal and mechanical deformations at different drying temperatures. A YSZ layer was also coated using R2R slot-die coating to o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Considering the poor doctoring quality at low doctoring pressure, we fixed the doctoring pressure to 0.6 MPa. The drying temperature was set to 150 °C considering the curing temperature of the ink according to the drying time, determined by the length of the dryer and the maximum web speed in this experiment [29,30]. Figure 4 presents the images of the ink particle at (a) room temperature and (b) cured at 150 °C, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the poor doctoring quality at low doctoring pressure, we fixed the doctoring pressure to 0.6 MPa. The drying temperature was set to 150 °C considering the curing temperature of the ink according to the drying time, determined by the length of the dryer and the maximum web speed in this experiment [29,30]. Figure 4 presents the images of the ink particle at (a) room temperature and (b) cured at 150 °C, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A roll-to-roll (R2R) additive manufacturing process is widely used in the flexible and stretchable electronic devices manufacturing because of the advantages of environmentally friendly, low cost and mass production [1][2][3]. Notably, the process is an excellent candidate to fabricate large-area flexible functional devices; many research groups have reported its superiority on the creation of large-area molecular diagnostic chip, fuel cells, organic photovoltaics, and flexible printed circuit board.…”
Section: Introductionmentioning
confidence: 99%